(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Crowdfunding is a new form of financing opportunities for small and medium enterprises and other innovators of creative business ideas by harnessing the power of the internet. As a new form of financing opportunity, this study investigated the influence of crowdfunding practices on entrepreneurship development and its marketing values on SMEs in Ogun state, Nigeria. Explanatory cross-sectional survey research design was employed and data analysis was carried out using SPSS 20. Analysis of the T-test was used to also ascertain the influence of crowdfunding on the entrepreneurship development in Nigeria. Findings from this research revealed that lack of awareness and understanding of crowdfunding as an instrument of raising funds by SMEs in Ogun state, Nigeria form the major challenges for SMEs in exploring the opportunities of the concept. This is evident from the model summary result in hypothesis one showing R square having 12%, which implies that Reward based, Loan based and Equity based crowdfunding which are the independent variables used only account for 12% variation in Business Growth of SMEs in Ogun state. Hypothesis two also indicates a 6% R square, which also implies that Reward based, Loan based and Equity based crowdfunding account for 6% variation in SMEs in Ogun state. The study recommends that government and campaigners of crowdfunding should launch national programs to educate the public about how crowdfunding works, how to assess campaigns, and how to use digital tools to explore opportunities crowdfunding offer.